An exploratory study of the Jola Ethnic culture and tourism promotion in the Gambia - Mutiu Kolawole Ambali; Admyre Sock (Borneo Novelty Publishing, 2025)
Purpose – This study aims to analyse the Jola tribe by examining its cultural dimensions, way of life, and key socio-cultural characteristics that shape communal associations, as well as to explore its potential within cultural tourism development.Design/Methodology/Approach – This research adopts a descriptive approach, drawing on conceptual definitions and cultural analysis to examine the fundamental elements that define the lifestyle and social organization of the Jola people.Findings – The findings reveal that the Jola ethnic group possesses a rich and distinctive cultural heritage, reflected in core lifestyle components such as the FUTAMPAF initiation ritual, traditional food and beverages, and unique entertainment practices. These elements play a significant role in sustaining communal identity and offer strong potential as cultural tourism assets for both local and international engagement.Originality/Value – This study contributes to the discourse on cultural tourism by highlighting the underexplored heritage of the Jola tribe and emphasizing its value as a cultural resource that can support tourism promotion and marketing in the contemporary tourism and hospitality industry.